A balancing act: Principles, criteria and indicator framework to operationalize social-ecological resilience of forests. (1st April 2023) - Nikinmaa, Laura; Lindner, Marcus; Cantarello, Elena; Gardiner, Barry; Jacobsen, Jette Bredahl; Jump, Alistair S.; Parra, Constanza; Plieninger, Tobias; Schuck, Andreas; Seidl, Rupert; Timberlake, Thomas; Waring, Kristen; et al.
Abstract: Against a background of intensifying climate-induced disturbances, the need to enhance the resilience of forests and forest management is gaining urgency. In forest management, multiple trade-offs exist between different demands as well as across and within temporal and spatial scales. However, methods to assess resilience that consider these trade-offs are presently lacking. Here we propose a hierarchical framework of principles, criteria, and indicators to assess the resilience of a social-ecological system by focusing on the mechanisms behind resilience. This hierarchical framework balances trade-offs between mechanisms, different parts of the social-ecological system, ecosystem services, and spatial as well as temporal scales. The framework was developed to be used in a participatory manner in forest management planning. It accounts for the major parts of the forest-related social-ecological system and considers the multiple trade-offs involved. We demonstrate the utility of the framework by applying it to a landscape dominated by Norway spruce ( Picea abies (L.) Karst.) in Central Europe, managed for three different management goals. The framework highlights how forest resilience varies with the pursued management goals and related management strategies. The framework is flexible and can be applied to various forest management contexts as part of a participatory process with stakeholders. It thus is an important step towards operationalizing social-ecological resilience in forest management systems. Highlights: Forest management goals determine the desired level of resilience. Participatory stakeholder engagement is crucial in operational resilience assessment. Our resilience framework allows projecting future scenarios for indicator analysis. Multiple trade-offs should be balanced to achieve resilience.